Delayed Harvesting Effects on the Cooking Qualities and Sensory Properties of Trifoliate Yam (Dioscorea dumetorum) Tubers - Abiodun, Olufunmilola Adunni; Akinoso, Rahman; Oladapo, Abiodun Sinmiat; Adepeju, Adefisola Bola (JOURNAL OF ROOT CROPS, 2015)
<!–[if gte mso 9]> <![endif]–>Cooking qualities and sensory attributes of trifoliate yam tubers harvested at different periods were evaluated. The tubers from two cultivars of trifoliate yam (white and yellow cultivars) were planted and harvested monthly from 7 to 11 months after vine establishment. The tubers at each period were peeled, washed and sliced and cooked in a water bath maintained at 100 ±2oC. The cooking qualities (water uptake ratio, cooking time and cooking loss, dry matter) and sensory properties of the boiled yam were determined. Water uptake ranged from 0.83 to 1.13, cooking time ranged from 49-97 min, cooking loss ranged from 0.87-2.38% and dry matter ranged from 31.85-45.34%. The yellow cultivar harvested at 11 months had higher water uptake and cooking time values of 1.13 and 97 min respectively, but there was no significant difference (p>0.05) in the values recorded for white trifoliate yam at 11 months. White trifoliate yam tubers had lesser cooking time than the yellow tubers at all harvesting periods. The soluble losses decreased with harvesting periods and loss was prominent at the earlier harvesting periods due to mealiness of the tubers. The sensory evaluation conducted on the boiled yam revealed that the yam tubers were very mealy and soft at 7 to 9 months but becomes soggy at 10-11 months. Delayed harvesting of the tubers had effect on the quality of the tubers. Harvesting of tubers at 7-9 months reduced post harvest losses and produced high quality food. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>